Entwicklung von topologieoptimierten Adapterelementen für die Fertigung mittels additiver Verfahren: Vereinigung von reinelektrischem Antriebsstrang mit konventionellem Chassis: Development of additively manufactured, topology‐optimized interface elements uniting an electrical drivetrain with a conventional chassis. Issue 5 (30th May 2018) - Sert, E.; Hitzler, L.; Merkel, M.; Öchsner, A.
Translation abstract: The individual mobility, as it was known for decades, is facing progressive challenges, with the major point being to facilitate a constantly increasing traffic volume without harming our ecosystem or putting people's health at risk. Yet, this alteration is expected to be fulfilled without cutting down on the luxury of individual mobility. A key element is the increase in traffic volume and the desire for individual mobility. The amount of exhaust gases increases significantly and leads to environmental pollution and has a negative impact on life quality in agglomerations and city centers. One approach to counteract this trend is the reduction of the exhaust emissions and the associated consumption of fossil fuels. The rethinking and the related increase in environmental awareness leads to a rising demand for electrically driven vehicles. Therefore, a number of requirements occur for the development and construction of future mobility solutions. One of the challenges, among others, is the development of modular and scalable power units in order to enable both the serial production of electrical drive trains in reasonable quantities and the electrical conversion of existing vehicles in a cost‐effective manner. The latter represents an intermediate step between the conventional and futuristic mobility and facilitates the implementation and testing of new approaches at lower cost and at an earlier stage. For the new construction of an electrically driven axle or the conversion of an existing axle to an electric drive, extensive tasks have to be carried out. Thereby, the use of topology optimization tools and additive production processes are essential.